The Influence of Future Time Perspective, Financial Risk Tolerance, and Knowledge of Financial Planning for Retirement on the Retirement Saving Behavior of SMEs Entrepreneurs in Sleman Regency - HC, R. Heru Kristanto; Nilmawati , Nilmawati; Gusaptono, R. Hendry (RSF Conference Series: Business, Management and Social Sciences, 2025)
Saving is a method effective in supporting future life, especially for SMEs that do not have pension insurance. This study analyzes the influence of future time perspective, financial risk tolerance, and knowledge of financial planning for retirement on retirement saving behavior, with gender as a moderating variable. The population is MSMEs in Sleman Regency. A total of 102 SMEs in Sleman Regency were selected using a specific sampling technique. The analysis technique with regression Moderation using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the study indicate that future time perspective and knowledge of financial planning for retirement have a positive effect on retirement saving behavior. Financial risk tolerance does not affect retirement saving behavior. Gender moderates the relationship between future time perspective, financial risk tolerance, and knowledge of financial planning for retirement on retirement saving behavior. Results study. This emphasizes the importance of future awareness, financial risk tolerance, and understanding of financial planning in shaping savings behavior. Providing policy recommendations to improve the financial readiness of SME entrepreneurs.